Mental Health in Afghanistan : Burden, Challenges and the Way Forward - Sayed, Ghulam Dastagir (World Bank, Washington, DC, 2013)
Afghanistan has been in internal and external strife for more than thirty years. Prolonged conflict and civil war have left millions dead, thousands with disabilities and massive internal and external population displacement. The situation has contributed negatively to every aspect of the country and society as the majority of the population has been traumatized by constant conflict, natural disasters, and the difficult Taliban years. There is ample evidence that these calamities have contributed to an increase in mental health problems and has been further complicated by growing level of drug abuse. As Afghanistan rebuilds itself, it is critical to understand the challenges and develop workable solutions. The paucity of high quality data on mental health problems and the lack of qualified human resources have hampered the development of cost-effective strategies and interventions to address the growing challenge of mental health in the country. There are few mental health facilities, and these facilities are scattered across the country with limited capacity and low levels of coverage. In addition, the population continues to face the main stressors with ongoing conflict in various parts of the country. To address mental health issues on a larger scale, this paper recommends public awareness-raising campaigns as a foremost prerequisite. It also proposes to draw on existing resources efficiently. Achieving the aforementioned objectives require political support by the Government of Afghanistan along with technical and financial support of the development partners. This will allow necessary expansion of mental health services and will build the capacity of mental health clinicians and public health experts in the country.